Decidual Neutrophil Infiltration Is Not Required for Preterm Birth in a Mouse Model of Infection-Induced Preterm Labor - Rinaldi, Sara F. (AAI, 2014)
Parturition is associated with a leukocyte influx into the intrauterine tissues; however, the exact role these leukocytes play in the onset of labor remains unclear. Neutrophil infiltration of the uteroplacental tissues has been particularly associated with infection-associated preterm labor (PTL) in both women and mouse models. In this study, we investigated the role of neutrophils in a mouse model of infection-induced PTL. Intrauterine administration of LPS on day 17 of gestation resulted in a 7-fold increase in the number of decidual neutrophils compared with control mice receiving PBS (p < 0.01; n = 8–11). We hypothesized that neutrophil influx is necessary for PTL and that neutrophil depletion would abolish preterm birth. To test this hypothesis, mice were depleted of neutrophils by treatment with anti–Gr-1, anti–Ly-6G, or the appropriate IgG control Ab on day 16 of gestation prior to LPS on day 17 (n = 6–7). Successful neutrophil depletion was confirmed by flow cytometry and immunohistochemistry. Neutrophil depletion with Gr-1 resulted in reduced uterine and placental Il-1β expression (p < 0.05). Neutrophil depletion with Ly-6G reduced uterine Il-1β and Tnf-α expression (p < 0.05). However, neutrophil depletion with either Ab did not delay LPS-induced preterm birth. Collectively, these data show that decidual neutrophil infiltration is not essential for the induction of infection-induced PTL in the mouse, but that neutrophils contribute to the LPS-induced inflammatory response of the uteroplacental tissues.